2013
DOI: 10.1177/1079063213480820
|View full text |Cite
|
Sign up to set email alerts
|

Catch Me If You Can

Abstract: The presumed dangers presented by sex offenders who have absconded from authorities have played a prominent role in public discourse surrounding state and federal sex offender management policy. The current study is the first to empirically investigate the characteristics of absconded sex offenders and explore how this group compares to other groups of sex offenders. Utilizing data from the Florida sex offender registry (N = 23,557), this exploratory study compares the characteristics and risk factors of absco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…When researchers assessed the impact of transience on registration compliance in Florida, they found that transients were more likely to become non-compliant, but not to abscond (Levenson, Ackerman, & Harris, 2013). When the RSOs did abscond, they were much more likely to do so from registration than from probation, suggesting that once out from under the watchful eye of probation officers, some transients disappear from their last known "address," perhaps willing to risk arrest in exchange for more civilized accommodations in the home of a friend or relative.…”
Section: Transience and Homelessnessmentioning
confidence: 97%
See 1 more Smart Citation
“…When researchers assessed the impact of transience on registration compliance in Florida, they found that transients were more likely to become non-compliant, but not to abscond (Levenson, Ackerman, & Harris, 2013). When the RSOs did abscond, they were much more likely to do so from registration than from probation, suggesting that once out from under the watchful eye of probation officers, some transients disappear from their last known "address," perhaps willing to risk arrest in exchange for more civilized accommodations in the home of a friend or relative.…”
Section: Transience and Homelessnessmentioning
confidence: 97%
“…In Florida, where residential restrictions render over 95% of residential dwellings off-limits for sex offenders in major metropolitan areas (Zandbergen & Hart, 2006, 2009), several homeless colonies have emerged around the state, and sex offenders who are forced to reside outdoors are instructed to register with law enforcement agents as “transient.” When researchers assessed the impact of transience on registration compliance in Florida, they found that transients were more likely to become non-compliant, but not to abscond (Levenson, Ackerman, & Harris, 2013). When the RSOs did abscond, they were much more likely to do so from registration than from probation, suggesting that once out from under the watchful eye of probation officers, some transients disappear from their last known “address,” perhaps willing to risk arrest in exchange for more civilized accommodations in the home of a friend or relative.…”
Section: Introductionmentioning
confidence: 99%
“…Policies that legislate offenders into homelessness undermine community safety by diminishing the chance for a successful reintegration. Moreover, transient sex offenders are more likely to abscond from registration, suggesting that housing restrictions may undermine the very purpose of registries (Levenson, Ackerman, & Harris, 2013). SORR laws can also cause sex offenders to cluster in the few locations where compliant housing is available, resulting in a disproportionate number of sex offenders in a small geographical area and leading to heightened concerns for the welfare of children living in such neighborhoods (Broward County Commission, 2009;FATSA, 2015;Socia, 2013).…”
Section: History Of Sex Offender Residence Restrictions (Sorrs) and Ementioning
confidence: 99%
“…Some even deliberately falsify their addresses or abscond from registration entirely, just so that they can fi nd a place to live (Levenson, Ackerman, & Harris, 2013 ;Socia et al, 2014 ). In this way, residence restriction may actually lower the effi cacy of other, already tenuous, post-incarceration sex offender sanctions, while lacking any established effectiveness of its own.…”
Section: Residence Restrictionsmentioning
confidence: 99%